Correlation between Workers’ Characteristics and Workplace Noise with Subjective Hearing Disorders in Textile Industry - Ratih Damayanti; Indah Lutfiya; Esfahani Refi Mirza (Universitas Airlangga, 2022)
Introduction: The textile manufacturing industry has a noisy work environment as a result of the weaving machines which have a noise intensity exceeding the threshold value. Noise can cause complaints of hearing disorders. Other factors that influence hearing disorders are agework period, and the use of ear protection equipment. This study aims to analyze the relationship between age, work period, the use of ear protection equipment, and noise intensity on complaints of subjective hearing disorders in the AJL Weaving Department of Textile Industry. Method: This research was a descriptive observational study with a cross sectional approach. Data were obtained by measuring noise intensity and distributing questionnaires to workers. Respondents in this study amounted to 45 people who were the total population of weaving operators and maintenance workers in the AJL Weaving Department of Textile Industry. Results: The results of this study indicate that age and work period have a sufficient relationship with complaints of subjective hearing disorders, while the use of ear protection equipment has a weak relationship with complaints of subjective hearing disorders, and noise intensity has a strong relationship with complaints of subjective hearing disorders. Conclusion: Individual characteristics only have a weak to moderate relationship with subjective hearing complaints. Meanwhile, exposure to noise intensity has a strong relationship with subjective hearing complaints.